P-018 MRI-based Endovascular Navigation in a Flow and Cadaveric Model; Feasibility Study. (26th July 2014) - Buciuc, R; Rube, M; Cox, B; Melzer, A
Abstract : Introduction/purpose: Currently endovascular navigation is performed by using fluoroscopy. This modality has some disadvantages such as, radiation, use of contrast and lack of visualization of brain parenchyma in "real time". The purpose of this study was to test the feasibility of navigating endovascular instruments on a flow model and in a cadaveric model using MR- based fluoroscopy. Materials and methods: The study was completed at the IMRI lab, University of Dundee, UK. The flow model consisted of an Elastrat flow model, coupled with a surgical heart pump with control for heart rate and output. For the cadaveric model three Thiel cadavers were used. The access of the cerebrovascular circulation was either through direct carotid access in one case or through a substernal incision and further navigation into the ascending aorta via the left ventricle (method described in a separate presentation). In one case venous access was also obtained through a direct approach to the right jugular vein and retrograde navigation into the superior sagittal sinus. The catheter used was a balloon catheter which was further connected to a suction component of the heart pump in an effort to reproduce the right heart function and avoid brain swelling. The position of catheters in the right and left internal carotid arteries as well as in the right vertebral artery was confirmed fluoroscopically. After access to the internal carotid artery the flow or cadaveric models were transferred to the MRI unit and testing of navigation was performed. For the flow model the heart pump was used to deliver fluid at a rate of 70 beats/min and a flow of 4 l/min. For the cadaveric model a single injection of Gadolinium 15 ml was elected to serve as the "roadmap" for intracranial navigation. MRI based pule sequences of 4 pulses/sec fluoroscopic equivalent were chosen. MRI multiplanar software as well as interventional MRI coils were also used for this experiment. Communication MRI-compatible equipment between the interventionalist and a "navigator" in the MRI console was used. For endovascular instruments, MR compatible Penumbra catheters were used. The wires were prototype non-metalic wires and the mechanical retriever was Acandis a German produced mechanical retriever. A Hydrocoil was also navigated to MCA bifurcation. Results: Visualization of flow as well as multiplanar "live" rendering of MR based roadmaps was possible on the flow and cadaveric model. For the flow model an artificially created clot was deployed in an M2 branch and successfully retrieved. For the cadaveric model navigation of Penumbra catheters was possible to the level of M1 segment. For the flow model a microcatheter was attempted to be navigated in an MCA bifurcation aneurysm. A hydrocoil was navigated through the microcatheter into the M1 segment of the flow model. Conclusion: MR-based endovascular navigation in the cerebro-vascular system is possible. Currently there are many limitations to the applicability of this technology in medical practice but the theoretical advantages make future efforts worthwhile. Disclosures: R. Buciuc: None. M. Rube: None. B. Cox: None. A. Melzer: None.